Enhanced luminescence properties of phosphors coated by silica nano-layers: Study of reflection and emission. Issue 2 (1st February 2019) - Rafiaei, Seyed Mahdi; Ashrafi, Fatemeh; Sayyadi-Shahraki, Ahmad; Karimzadeh, Elmira
Abstract: We present a comprehensive investigation of the YVO4 :1 mol% Eu 3+ phosphor, synthesized via a facile solid-state approach. Different amounts of TEOS were used to coat the surface of phosphors by SiO2 via sol-gel method. It was found experimentally that covering the surface of phosphors by specific amounts of silica results in the improvement of phosphors emission intensity. Individually, by calculating the reflection coefficient of YVO4 and YVO4 /SiO2 phosphors and also using the classical electromagnetic concepts, it was shown that the existence of silica layers on YVO4 particles reduces the reflection of the excitation beam, which is in good agreement with the reinforced emission behavior. Experimentally, upon the collision of UV light with the wavelength of 310 nm, the strongest photoluminescence emission is achieved when the thickness of the SiO2 layer is approximately 50 nm. This result is consistent with the optimum thickness calculated via the reflection coefficient and also the Beer-Lambert law.